Treatment of Moya Moya disease using indirect surgery technique - Cezary Grochowski; Bartłomiej Kulesza; Dariusz Szczepanek (Kazimierz Wielki University, 2016)
Grochowski Cezary, Kulesza Bartłomiej, Szczepanek Dariusz. Treatment of Moya Moya disease using indirect surgery technique. Journal of Education, Health and Sport. 2016;6(8):236-240. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60391 http://ojs.ukw.edu.pl/index.php/johs/article/view/3752       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 25.07.2016. Accepted: 12.08.2016.     Treatment of Moya Moya disease using indirect surgery technique   Cezary Grochowski1, Bartłomiej Kulesza2, Dariusz Szczepanek2   1Internship in SPSK nr. 4 in Lublin 2Department of Neurosurgery, Medical University of Lublin   Abstract   Introduction: Moya Moya disease is a rare health condition with unknown etiology. Because of the pathological process in the patient vessels we can observe narrowing or occlusion of distal part of internal carotid artery and proximal part of anterior and medial cerebral artery, which is characteristic for this disease. The disease occurs most often among asian women and it usually affects patients in their first decade of life or 3-4 decade. Case presentation: Four year old female suffered from headaches, dizziness as well as progressive paroxysmal hemiparesis and speech disorder. The symptoms were recurrent and lasted for two years. MRI and MRA were performed and revealed pathological changes in arteries of scull base and pathological collateral arteries, characteristic for moyamoya disease. Surgical treatment: Multiple burr hole surgery was performed. Holes were made in the left fronto-temporo-parietal area, peritoneal straps were inserted into the subarachnoidal area in order to start revascularization process. Conclusion: Presented technique is preferred among children suffering from moya moya disease because of the safety of the technique and good treatment effects. There is no need to perform by-pass surgery which is also considered as big advantage of presented technique.